Actinotignum schaalii (formerly Actinobaculum schaalii): a newly recognized pathogen—review of the literature. (January 2016) - Lotte, R.; Lotte, L.; Ruimy, R.
Abstract: The genus Actinotignum contains three species, Actinotignum schaalii (formerly Actinobaculum schaalii ), Actinotignum urinale and Actinotignum sanguinis. A. schaalii is the species most frequently involved in human infections, with 172 cases, mostly urinary tract infections (UTIs), reported so far. Invasive infections have also been described. This facultative anaerobic Gram-positive rod is part of the urinary microbiota of healthy patients. It is responsible for UTIs, particularly in elderly men and young children. A. schaalii is an underestimated cause of UTIs because of its fastidious growth on usual media and difficulties associated with its identification using phenotypic methods. Indeed, this slow-growth bacterium requires blood-enriched media and an incubation time of 48 hours under anaerobic or 5% CO2 atmosphere. Furthermore, only matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF) or molecular-based methods allow the accurate identification of this bacteria. MALDI-TOF using Microflex LT with the Biotyper database (Bruker Daltonics, Bremen, Germany) is the most reliable technology for the routine identification of A. schaalii. The identification of this uropathogen is all the more important because it is resistant to trimethoprim/sulfamethoxazole and second-generation quinolones that are widely used in the treatment of UTIs. Antimicrobial therapy using β-lactams prolonged for up to 2 weeks is the most efficient treatment and should be recommended. Microbiologists should assess the presence of A. schaalii in urine using appropriate culture and identification methods in the case of a direct examination that is positive for small coccoid rods, a negative nitrite urinary stick associated with leukocyturia, treatment failure with trimethoprim/sulfamethoxazole or fluoroquinolones, or undocumented, repeated UTIs.